Synthesis and characterization of a holmium 2, 2′-bipyridine-5, 5′-dicarboxylate MOF: Towards the construction of a suitable holmium carrier. (1st February 2019) - Vizuet, Juan P.; Lewis, Abigail L.; McCandless, Gregory T.; Balkus, Kenneth J.
Graphical abstract: The synthesis and characterization of a holmium-bipyridine-dicarboxylate MOF is reported. The extended framework contains uncoordinated N atoms from the pyridine rings and high holmium content, making this MOF a potential holmium carrier for radiotherapeutic applications. Abstract: Based on the 2, 2′-bipyridine-5, 5′-dicarboxylic acid ligand (H2 bpdc), a new metal–organic framework using holmium as the coordinating metal site was synthesized through a solvothermal reaction. The 3D compound [Ho2 (bpdc)3 (DMF)2 ]·2(DMF) n (1 ) was characterized by single crystal X-ray diffraction, FTIR, TGA and PXRD. The coordination between H2 bpdc, the solvent, and holmium (CN = 7) allows for the construction of a MOF containing potentially free metal sites and uncoordinated N-donor sites. These features make this MOF an attractive holmium carrier for radiotherapeutic applications.